How and When Does the Second Language Influence the Production of Native Speech Sounds: A Literature Review. (September 2016) - Kartushina, Natalia; Frauenfelder, Ulrich H.; Golestani, Narly
Abstract : In bilinguals and second language learners, the native (L1) and nonnative (L2) languages coexist and interact. The L1 influences L2 production via forward transfer, as is seen with foreign accents. However, language transfer is bidirectional: even brief experience with an L2 can affect L1 production, via backward transfer. Here, we review the growing literature on backward transfer at the phonetic level and identify various factors that modulate it. Indeed, a multitude of interrelated factors have been shown to determine the strength of backward transfer, including L2 related factors (age of L2 acquisition, L2 pronunciation skill and proficiency, stage of learning, immersion), L1 related factors (amount and circumstances of L1 use), and factors related to both L1 and L2 (language similarity and individual differences). Controlled longitudinal, laboratory studies are required in conjunction with naturalistic ones to tease apart the influences of these different factors on L1 speech.